Condom Use Practices for HIV Prevention Among Men Who Have Sex with Men in Banjarnegara - Calista Haryani; Novia Handayani; Ratih Indraswari (Master Program of Health Promotion Faculty of Public Health Diponegoro University, 2026)
Background: Men who have sex with men (MSM) are a key population at high risk of HIV AIDS transmission, largely due to inconsistent condom use. This study analyzes determinants of condom use behavior among MSM in Banjarnegara Regency using Lawrence Green’s theoretical framework.Method: A cross-sectional study was conducted with 115 respondents. Respondents in this study were MSM residing in Banjarnegara. Respondents were selected based on inclusion and exclusion criteria. The inclusion criteria were MSM who had sexual intercourse in the last month, while the exclusion criteria were MSM who were Field Officers (PL) and MSM who were HIV AIDS positive. The sampling technique used in this study was purposive sampling. Data collection was conducted using a questionnaire method. Data were collected via questionnaires and analyzed using Chi-square tests and logistic regression.Result: Condom use remains low, with 47.8% of respondents not using condoms consistently. Bivariate analysis showed a significant association with marital status (p=0.007; OR=6.62), occupation (p=0.001; OR=2.3), attitude (p=0.001; OR=3.51), community support (p=0.000; OR=4.62), and partner support (p=0.003; OR=3.77 Multivariate analysis identified attitude as the dominant factor (p=0.021; OR=2.856). These findings conclude that the formation of positive attitudes plays a central role in increasing consistent condom use among MSM. Therefore, it is recommended that HIV prevention programs focus on strengthening attitudes, increasing community and partner support, and optimizing safe sexual behavior education among the MSM population.